Social Network Analysis dalam Komunikasi Pembelajaran Inklusif Sekolah Tinggi Global: Sebuah Kajian Literatur Review - Sopiyani Solihah; Muhamad Anang Rivai; Munajar, Munajar; Diah Ajeng Purwani; Sumarsono (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Inclusive education in higher education faces serious challenges, particularly in relation to communication, which has not been able to ensure equal participation of students with disabilities. Globally, only about 30% of SDG targets related to disability are on track for achievement. This indicates a gap between inclusive education policy and practice. In the big picture of this study, communication is positioned as a key element that connects inclusive pedagogy, collaborative learning, accessibility, and student learning outcomes. This study aims to map trends, actors, centrality, and patterns of research collaboration and networks between countries, authors, and organizations during the period 2015–2025. The methods used were a systematic bibliometric-based literature review and Social Network Analysis (SNA) of 242 Scopus documents as the population, with 92 articles selected as samples using PRISMA and visualized using VOSviewer. The results show a sharp increase in publications since 2021, peaking in 2025, with the keywords higher education, inclusive education, communication, and disability at the center of the network. The global collaboration network is dense but dominated by Global North countries. In addition, inclusive communication acts as the main mediator between pedagogical strategies and student learning outcomes. This study recommends strengthening equitable collaboration and context-based research in the Global South to enrich the discourse on global inclusive education.